2015
DOI: 10.1111/plb.12339
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic and jasmonic acid pathways are necessary for defence against Dickeya solani as revealed by a novel method for Blackleg disease screening of in vitro grown potato

Abstract: Potato is major crop ensuring food security in Europe, and blackleg disease is increasingly causing losses in yield and during storage. Recently, one blackleg pathogen, Dickeya solani has been shown to be spreading in Northern Europe that causes aggressive disease development. Currently, identification of tolerant commercial potato varieties has been unsuccessful; this is confounded by the complicated etiology of the disease and a strong environmental influence on disease development. There is currently a lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…Jasmonates and SA are essential phytohormones for plant development and survival, and play an important role in plant resistance to fungal diseases [50, 51]. COI1 is a key component of the JA-mediated signal transduction pathway, leading to the dissociation between JAZ and the transcription factor MYC2, which could induce defense-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Jasmonates and SA are essential phytohormones for plant development and survival, and play an important role in plant resistance to fungal diseases [50, 51]. COI1 is a key component of the JA-mediated signal transduction pathway, leading to the dissociation between JAZ and the transcription factor MYC2, which could induce defense-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors found that the JA signalling pathway is also involved in susceptibility since the JA insensitive jai1 and spr2 mutants were more resistant, while prosystemin overexpressing plants, that have increased systemin, which triggers JA biosynthesis, were more susceptible to A. alternata infection (Jia et al 2013 ). In potato, both SA and JA pathways were shown to be required for foliar and tuber defence against the necrotrophic bacterial pathogen Dickeya solani, one of the causal agents of blackleg disease (Burra et al 2015 ). Additionally, it is becoming increasingly evident that not only the JA and SA signalling pathways are important in the host defence against necrotrophs, but that the plant hormones abscisic acid (ABA) and auxin (IAA) can also modulate host defence against necrotrophs (Mengiste 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 contain information about number of plants or tubers that were investigated in each phenotype study, and under what conditions it was carried out. Dickeya scoring of in vitro plants was done according to [33]. P. infestans resistance on tubers (tuber blight) were assessed as described in [21], and the Phytophthora resistance data on leaves (late blight) is described in Lenman et al 2016.…”
Section: Plant Growth Phenotyping Sample Collection and Preparationmentioning
confidence: 99%